2017
DOI: 10.7150/ijms.18288
|View full text |Cite
|
Sign up to set email alerts
|

In vivo application of Granulocyte-Macrophage Colony-stimulating Factor enhances postoperative qualitative monocytic function

Abstract: BACKGROUND: Granulocyte macrophage colony-stimulating factor (GM-CSF) can be used as a potent stimulator for immune suppressed patients as defined by a decrease of human leukocyte antigen-D related expression on monocytes (mHLA-DR) after surgery. However, the exact role of GM-CSF on monocytic and T cell function is unclear. METHODS: In this retrospective randomized controlled trial (RCT) subgroup analysis, monocytic respectively T cell function and T cell subspecies of 20 immune suppressed (i.e. mHLA-DR levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Basic patient characteristics, intraoperative- and outcome parameters are shown in Table 1 . Some of the results were already shown to analyze group differences after postoperative immune stimulation 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic patient characteristics, intraoperative- and outcome parameters are shown in Table 1 . Some of the results were already shown to analyze group differences after postoperative immune stimulation 23 .…”
Section: Resultsmentioning
confidence: 99%
“…This retrospective subgroup analysis of a previously published study of our research group 22 , 23 investigated innate and acquired immune cells as well as monocytic and T cell immune function during severe postoperative immune suppression (mHLA-DR ≤ 10,000 antigens per cell on pod1) that were measured in 10 out of 20 patients of the placebo group of the bigger cohort until pod5 after elective esophageal or pancreatic resection (measurement had to be stopped after 10 patients for economic reasons, no selection of the patients; Figure 1 ). All patients received guideline-based anesthesiological and surgical treatment according to our standard operating procedures 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GM-CSF treatment increased expression of HLA-DR on monocytes in immunosuppressed patients after surgery; GM-CSF treated group had fewer days with infection compared to placebo and influenza vaccination as a treatment [ 34 ]. A subsequent analysis of this trial showed that, in addition to increased HLA-DR, monocytes from GM-CSF treated patients showed increased release of LPS-induced TNF [ 35 ]. These results suggest a potentially clinically relevant role for the GM-CSF induction of HLA-DR.…”
Section: Discussionmentioning
confidence: 99%
“…We and others used mHLA-DR expression to stratify immune compromised patients after surgery [ 18 , 19 ] and during severe sepsis [ 20 ]. In both settings, mHLA-DR could be increased through administration of GM-CSF restoring immune function and improving outcome.…”
Section: Introductionmentioning
confidence: 99%